PENGGUNAAN DISTRIBUSI LABA DALAM MENDETEKSI MANAJEMEN LABA - Yulianti, Yulianti (Jurnal Akuntansi dan Keuangan Indonesia, 2004)
Discontinuities in earnings distribution have been discovered by several studies in United States and Australia. These studies examined the pooled, cross sectional distribution of earnings and found discontinuities around earnings threshold which indicates the exercise of management discretion to exceed earnings threshold. This study examines the distribution of earnings in Indonesia for two important purposes which are avoiding losses and avoiding earnings decline. The result on listed companies at the JSX during 1999 - 2002 show abnormality in earnings distribution, whereas total small profit firms are above expectations, meanwhile total small loss firms are the opposite. We didn’t find such abnormality in the distribution of earnings changes, whereas total small decrease firms in contrary are above expectations. This suggests that the most important earnings threshold for Indonesian firms is to avoid reporting losses.